1969
DOI: 10.1161/01.res.24.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucagon on Atrioventricular Conduction and Ventricular Automaticity in Dogs

Abstract: The effects of glucagon, 50 µ/kg, on atrioventricular (A-V) conduction and ventricular automaticity were studied in 14 dogs. Atrial pacing was used to control the heart rate. The His bundle electrogram was recorded, and the interval from the pacing impulse (P) to the His bundle spike (H), the P-H interval, was used as a measure of A-V conduction. Ventricular automaticity was estimated in four dogs by recording vagal escape time and idioventricular rate after 60 seconds of continuous vagal stimulation. In three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
19
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 15 publications
5
19
0
Order By: Relevance
“…We demonstrated a slight reduction in atrioventricular conduction time in our patients; this is supported by Steiner et al [22], who showed a 30-percent reduction in conduction through the atrioventricular node in dogs paced at a rate of 250/min.…”
Section: Discussionsupporting
confidence: 89%
“…We demonstrated a slight reduction in atrioventricular conduction time in our patients; this is supported by Steiner et al [22], who showed a 30-percent reduction in conduction through the atrioventricular node in dogs paced at a rate of 250/min.…”
Section: Discussionsupporting
confidence: 89%
“…6, 12 The similarity between the cardiovascular effects of glucagon and the catecholamines 8 , 11 has caused interest in the circulatory effects of glucagon. Studies have been carried out on the effects of glucagon on myocardial contractility/-6, 10, 14 on A-V conduction/' 17 and on heart rate. 6 , 17,18 The effect of glucagon also has been studied on the isolated heart and on conscious dogs after an experimental myocardial infarction.…”
Section: Veterans Administration Hospitalmentioning
confidence: 99%
“…The mechanism of the positive inotropic action has not been clarified. Beta-blocking agents do not abolish the action (1)(2)(3)(4). It has also been reported that the glucagon effect is unaltered by catecholamine depletion due to treatment with reserpine (2).…”
mentioning
confidence: 96%